PENGARUH KUALITAS PELAYANAN TERHADAP KEPATUHAN MASYARAKAT DALAM MEMBAYAR PAJAK KENDARAAN BERMOTOR DI KANTOR SAMSAT STABAT KABUPATEN LANGKAT - Reza Irfanka; Dara Aisyah (Smart Education, 2023)
This study aims to determine the quality of service and public compliance in paying Motor Vehicle Tax at the Samsat Stabat office, Langkat Regency, as well as analyzing the effect of service quality on public compliance in paying Motor Vehicle Tax by testing Rahayu theory who said that there was an effect of service quality on tax compliance. The type of research used is associative research (relationship) using quantitative data analysis. The population and sample in this study were taxpayers who were registered at the Samsat Stabat office in Langkat Regency were totaling 100 people. The research instrument used a questionnaire with a Likert scale. Data analysis was performed using Structural Equation Modeling (SEM) using Partial Least Square (PLS) program. SEM consists of 2 models such as measurement model (outer model) and structural model (inner model). Both models test the validity, reliability and research hypotheses. The results showed that the service quality was in the high or appropriate category. Compliance with paying Motor Vehicle Tax is in the high category. and the quality of service has a positive and significant effect on public compliance in paying Motor Vehicle Tax (PKB) at the Stabat Samsat Office of Langkat Regency. The coefficient of determination R Square is 0.869 indicating the magnitude of the effect of service quality on compliance with paying Motor Vehicle Tax (PKB) 86.9% and 13.1% influenced by other factors not examined in this study.